2020
DOI: 10.7717/peerj.9642
|View full text |Cite
|
Sign up to set email alerts
|

Air quality improvement during triple-lockdown in the coastal city of Kannur, Kerala to combat Covid-19 transmission

Abstract: The novel SARS-CoV-2 coronavirus that emerged in the city of Wuhan, China, last year has since become the COVID-19 pandemic across all continents. To restrict the spread of the virus pandemic, the Government of India imposed a lockdown from 25 March 2020. In India, Kannur district was identified as the first “hotspot” of virus transmission and a “triple-lockdown” was implemented for a span of twenty days from 20 April 2020. This article highlights the variations of surface O3, NO, NO2, CO, SO2, NH3, VOC’s, PM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…However, lower O 3 concentration during the night is due to inhibition of photochemistry, titration of O 3 by surface emissions of NO, and loss due to surface deposition (Mallik et al 2015). The pronounced elevated diurnal pattern during L1 suggests a higher rate of photochemical production of O 3 from precursors compared to O 3 destruction (Resmi et al 2020). The O 3 chemistry during L1 could be due to locally/regionally emitted precursors along with atmospheric transport from the Chota-Nagpur region and the north-western parts of Odisha state (Fig.…”
Section: Diurnal Variability Of Air Pollutantsmentioning
confidence: 99%
“…However, lower O 3 concentration during the night is due to inhibition of photochemistry, titration of O 3 by surface emissions of NO, and loss due to surface deposition (Mallik et al 2015). The pronounced elevated diurnal pattern during L1 suggests a higher rate of photochemical production of O 3 from precursors compared to O 3 destruction (Resmi et al 2020). The O 3 chemistry during L1 could be due to locally/regionally emitted precursors along with atmospheric transport from the Chota-Nagpur region and the north-western parts of Odisha state (Fig.…”
Section: Diurnal Variability Of Air Pollutantsmentioning
confidence: 99%
“…Other potential impacts of lockdowns on personalized exposure to UV light could be mediated by changes in air pollution levels, with increases in solar radiance observed in some Indian cities in which particulate matter levels reduced by >50% during lockdowns of March–April 2020 ( 68 ). Insolation (the amount of solar radiation reaching the earth's surface) increased by 8% in Delhi (North India) in late March 2020 (during national lockdown) compared to previous years, which was determined by measuring the amount of UV radiation received by solar panels ( 69 ).…”
Section: Uv Light Sun Exposure and Covid-19mentioning
confidence: 99%
“…Insolation (the amount of solar radiation reaching the earth's surface) increased by 8% in Delhi (North India) in late March 2020 (during national lockdown) compared to previous years, which was determined by measuring the amount of UV radiation received by solar panels ( 69 ). Similarly, in Kannar (South India), solar radiation levels (measured using a pyranometer) during lockdown increased by 7% ( 68 ). Anecdotal evidence from media reports suggests that Indian citizens were recommended to seek sun exposure during social isolation in April, 2020 ( 70 ).…”
Section: Uv Light Sun Exposure and Covid-19mentioning
confidence: 99%
“…In addition, SO 2 emissions registered a decrease (−19%), which was identified in China as a decrease attributed to lower emissions from traffic and coal combustion [62]. Kannur, India, reported decreased emissions (−62%), and a diurnal variation most pronounced during peak traffic hours was absent during the lockdown owing to the roads being deserted [70]. Figure 4 shows NO 2 emissions increased in the northern Colombian region due to events of long-range pollution transport, like regional biomass burning beginning at the end of March, during the lockdown, according to recent studies [33,34]; the air quality improvement shown in this period was partially annulled by the impact of these events.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, acidifying gases (NH 3 , SO 2 ) also showed a significant emissions reduction, up to −23% for NH 3 . Other studies found that decreasing emissions were identified in Kannur district, India (−16%), due to a complete shutdown of traffic and industrial activities [70], as NH 3 emissions come mainly from heavy-duty diesel vehicles [65]. In addition, SO 2 emissions registered a decrease (−19%), which was identified in China as a decrease attributed to lower emissions from traffic and coal combustion [62].…”
Section: Discussionmentioning
confidence: 97%